Taking it to practice: Building a critical postmodern theory of adult learning community. - Andre P. Grace (Adult Education Research Conference, 1997)
This paper considers research themes important to contemporary Canadian federal HRD (human resource development) policy, research, and experimentation. It takes up security, work, and learning concerns affecting today's citizen workers and learners and develops aspects of a critical postmodern theory of adult learning community.